Imiquimod enhances excitability of dorsal root ganglion neurons by inhibiting background (K2P) and voltage-gated (Kv1.1 and Kv1.2) potassium channels - Lee Jaekwang; Kim Taekeun; Hong Jinpyo; Woo Junsung; Min Hyunjung; Hwang Eunmi; Lee Sung; Lee C Justin (SAGE Publishing, 2012)
Abstract Background Imiquimod (IQ) is known as an agonist of Toll-like receptor 7 (TLR7) and is widely used to treat various infectious skin diseases. However, it causes severe itching sensation as its side effect. The precise mechanism of how IQ causes itching sensation is unknown. A recent report suggested a molecular target of IQ as TLR7 expressed in dorsal root ganglion (DRG) neurons. However, we recently proposed a TLR7-independent mechanism, in which the activation of TLR7 is not required for the action of IQ in DRG neurons. To resolve this controversy regarding the involvement of TLR7 and to address the exact molecular identity of itching sensation by IQ, we investigated the possible molecular target of IQ in DRG neurons. Findings When IQ was applied to DRG neurons, we observed an increase in action potential (AP) duration and membrane resistance both in wild type and TLR7-deficient mice. Based on these results, we tested whether the treatment of IQ has an effect on the activity of K+ channels, Kv1.1 and Kv1.2 (voltage-gated K+ channels) and TREK1 and TRAAK (K2P channels). IQ effectively reduced the currents mediated by both K+ channels in a dose-dependent manner, acting as an antagonist at TREK1 and TRAAK and as a partial antagonist at Kv1.1 and Kv1.2. Conclusions Our results demonstrate that IQ blocks the voltage-gated K+ channels to increase AP duration and K2P channels to increase membrane resistance, which are critical for the membrane excitability of DRG neurons. Therefore, we propose that IQ enhances the excitability of DRG neurons by blocking multiple potassium channels and causing pruritus.